Bridging the gap between research and extension - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Making the Link. Agricultural Research and Technology Transfer in Developing Countries, edited by David Kaimowitz, Westview special studies in agriculture science and policy , 1980 ISBN 0 8133 7896